Analysis of Bioactive Content in Indonesian Local Superfoods as a Preventative of Degenerative Diseases - Tambunan, Elen Christ (Journal of Pharmacopoeia, 2025)
Degenerative diseases such as diabetes, cancer, and heart disease pose a major challenge to modern public health. One potential preventative measure is the use of local Indonesian superfoods rich in bioactive compounds. This study aims to identify the main bioactive compounds in various local Indonesian superfoods and explore their potential in preventing degenerative diseases. The research method used was a qualitative one with a literature study approach obtained from scientific journals, research reports, and interviews with nutritionists and food experts. Data analysis was conducted through content analysis with categorization of bioactives and their relationship to disease prevention mechanisms. The results showed that local superfoods such as moringa, tempeh, purple sweet potato, turmeric, ginger, mangosteen, guava, and soursop contain important bioactives such as flavonoids, polyphenols, isoflavones, anthocyanins, curcumin, gingerol, and acetogenins. These compounds act as antioxidants, anti-inflammatories, immunomodulators, and protective agents for cells, thus having significant potential in preventing degenerative diseases. These findings confirm that local Indonesian superfoods have strategic value not only as functional foods, but also as part of preventive public health efforts and national food sovereignty.